Impact of Safety Management Practices on Safety Compliance Behavior with Mediation of Safety Motivation (Patan Pragya, 2023)
Construction projects have many work-related health accidents and injuries, which cost the organization financially and non-financially. Safety management practices play a significant role in overcoming such safety problems. This study aims to examine the influence of safety management practices on safety compliance in construction sites. The study was conducted through questionnaire surveys with 97 respondents from construction sites in Surabaya, Indonesia. Partial least squares structural equations modeling (PLS-SEM) was used to analyze the conceptual model. The research findings suggest management to uplift their workplace safety practices. Furthermore, contractors involved in construction projects can implement health and safety practices to reduce accidents.